THE WRITING OF INSURANCE ADMINISTRATION SYSTEM RESEARCH AT PT. INSURANCE ATERINDO - Diyah Suryatri; Ir. Fitri Sjafrina, MMSi (Jurnal Sistem Informasi, 2000)
PT. Insurance Arterindo with three divisions in it requires computers to help thereceiving, processing and storage of data required in system administration work inthe company. In the writing of this research will provide information about theapplication process prospective customers as well as due process insurance paymentsmade by the administration with the help of Microsoft Access.Use Microsoft Access to enter data in clients, help a particular parties when needed toprocess premium payments and compensation process to the customer itself. Alsolisted in the file of customer data.